Substantiation оf Methods to Remove Water Inflows in Wells Draining Gas Condestate Deposits - E. V. Vaganov; S. K. Sokhoshko; I. I. Krasnov (Наука. Инновации. Технологии)
Introduction. Forecasting the intrusion of formation waters into the reservoir determines the time of watering wells and, therefore, is necessary for planning and implementing measures to limit water inflows. The study of the geological structure of gas and gas condensate deposits during the development of oil and gas condensate fields makes it possible to identify the main causes of the occurrence and development of water cut in well production. The forecast is based on the study of the ways of breakthrough of bottom and contour water from the aquifer. Also, in the process of hydrochemical control, it was determined that water breakthrough occurs due to the rise of the GWC and the violation of the tightness of the annulus [1, 2].Materials and research methods. On the basis of field studies, it was shown that the depression funnel in the current period of development in the Aptian-Cenomanian aquifer complex was formed as a result of the exploitation of gas deposits in the Urengoyskaya and Yen-Yakhinskaya areas [3, 4]. According to the methodology of I.P. Cholovsky, the entropy of reservoirs was determined by dissection as a measure of heterogeneity in the interval of opening a productive reservoir. As a result of the analysis, the mechanism of well watering in the area of distribution of the factors of net-to-grossness and heterogeneity was revealed [5–7]. It has been determined that the intensity of water intrusion largely depends on the porosity and permeability properties (PRP) of the rocks of the deposit and the watershed. Therefore, the rate of GWC rise and the change in saturation are associated with the features of the lithological and tectonic structure of the section within individual sections of the deposit of operating production wells [8, 9].Research results and their discussion. Most of the wells in operation at the Urengoyskoye field have a minimum porosity factor of 24%, and the net-to-gross ratio of the reservoirs in the formation interval is at least 85%. The analysis of the geological structure during the development of gas deposits in the Urengoyskaya and Yen-Yakhinskaya areas made it possible to determine the causes of the occurrence and development of water cut in well production. It is based on the study of the ways in which formation waters enter the well from the aquifer. Irregularity in thickness and area, as well as significant sandiness of clay layers causes a close hydrodynamic relationship of the layers. Therefore, the weighted average values of the analyzed parameters can be taken as the boundary conditions for predicting watering and putting the well into operation after carrying out measures to limit water flow. To predict the success of waterproofing work, an analysis of the geological factors of sand content and heterogeneity along the section was also carried out. As a measure of heterogeneity in the perforation interval, the entropy of reservoirs was determined by stratification. According to the chemical analysis of samples taken from the wells, geophysical studies of the current position of the GWC and the results of measures to limit the inflow of water (WRI), the boundaries of the sectors were determined.Conclusions. Forecasting well watering at this stage of development of gas deposits in the Far North fields is very relevant, as it necessitates the formulation and solution of the problem of production and treatment of natural gas with a high content of formation water in well production. Based on the results of the analysis of the reasons for the downtime of the well stock, taking into account the geological structure, the location of clay interlayers and the permeability of productive horizons, it is recommended to carry out geological and technical measures (GTO) on the wells. Thus, for wells with sufficiently thick shale interlayers up to 5.0 meters, it is necessary to carry out (MOW) by installing cement bridges in the zone of shale interlayers. It is also recommended to re-perforate and then re-inject the water-proofing composition with additional cement in wells with clay interlayers of a small thickness of more than one meter with alternating productive interlayers of small thickness.